SOME REMARKS ON THE HIGHEST WIND SPEED VALUES IN LUBLIN - Nowosad, Marek; Dobek, Mateusz; Kieliszek, Adam; Siwek, Krzysztof (Bulletin of Geography. Physical Geography Series, 2009)
This paper presents and analysis of the highest wind speed values recorded at the Meteorological Observatory of the Maria Curie-Skłodowska University in Lublin. The study uses values recorded data (3 times a day) for the period 1981–2005. During the 25 years of the study period there were 19 occasions of wind speed ≥ 10 m·s-1 and 14 cases of winds gusting at or over 20 m·s-1. Both kinds of situation were noticed most often in January and did not occur in May, June, July or August.